Peran Strategis Manajemen Sumber Daya Manusia Global dalam Meningkatkan Kinerja Perusahaan Multinasional - Wahyu Kristia Ningsih; Riska Nur Cahaya; Aurora Sheyra Nazhwa Izzaty; Adinda Arraudhah Khanza Rahmania (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Globalization requires multinational corporations to effectively manage human resources in different countries with different cultural, legal, and policy backgrounds. Global Human Resource Management (HRM) is key in improving organizational performance through cross-country talent management, global leadership development, and the implementation of adaptive HR policies. This article discusses how global HRM strategies contribute to improving company performance with relevant case studies and theories.